Pelatihan dan Praktik Penulisan Makalah dan Jurnal Ilmiah bagi Mahasiswa Prodi Manajemen Pendidikan Islam - M, Ansharuddin; Sholihan, Sholihan (PT. Cahya Edupreneur Indonesia, 2023)
Based on initial observations in January 2022 of students of the Islamic Education Management Study Program Semester 4 and 6 at STAI Hasan Jufri Bawean it was found that there were still several students who had limited abilities in preparing and writing papers in the form of papers or scientific journal articles and the prevalence of plagiarism models. Therefore, there is a need for training and hands-on practice in writing scientific articles for students, both papers and scientific journals. This activity was attended by 21 students in semester 4 and 6 of the Islamic Education Management Study Program, STAI Hasan Jufri Bawean. The activity method used is workshops and hands-on practice. The results of this community service activity are increasing students' understanding of the types of scientific papers, the rules for writing scientific papers, and being able to write articles both papers and journal articles in a professional manner according to the guidelines for writing scientific papers.